Dinâmica produtiva e inovativa no arranjo produtivo local de ovinocaprinocultura de Sergipe : o caso da Associação Sergipana dos Criadores de Caprinos e Ovinos - ASCCO - Oliveira, Thiago de Souza (2014)
From the theory of regional / local endogenous, arising from the 1980´s development, it creates a new concept of development, where the the dynamics of the regions would be linked to internal factors. From this emerges a set of theories that explain the regional / local development from clusters of small producers. In Brazil, the concept of Local Productive Arrangement to represent a set of economic, political factors and members located in the same territory, developing related economic activities and presenting links production, interaction, cooperation and learning emerges. To be specific, since each APL has a specific set of actors, focusing on a specific economic activity and particular advantages and challenges, it is necessary to productive each cluster is studied individually in order to understand its dynamics, understand their limitations and outline the necessary for their development strategies. In Sergipe, the State Center for Local Productive Arrangements identified 17 production clusters, including the Local Productive Arrangement of Sheep and Goat Farming. This productive activity, nationally, is found in all regions and marked recently by a new configuration, where the South is no longer the largest holder of the national herd and the Northeast begins to take the lead with respect to the number of animals. The growth rates of the herd of Northeast surpass the national average and the rates of growth of Sergipe flock outperform the regional average. The APL ovinocaprinocultor sergipano located in areas with low economic dynamism, low social indicators and problems related to drought. The social role of economic activity justifies studied dissertative work to deepen the knowledge about the production activity in the state. The growth in Sergipe herd is due to some factors and the objective of this study was to examine how the Sergipana Breeders Association of Sheep and Goats contributes to the development of productive activity. With this, we identified that the ASCCO presents itself as a key to the development of productive activity in the state link. The breeding program, the main activity of the association, is nationally recognized and should continue to be promoted by the partner institutions, although the relationships between producers, as a whole, are incipient. Moreover, ASCCO operates in the link between producers and funding agencies, does a good job of promoting trade and contributes in opening new markets.